Lead‐Free Halide Perovskites for Direct X‐Ray Detectors - Xiangshun Geng; Yu‐Ang Chen; Yuan‐Yuan Li; Jun Ren; Guan‐Hua Dun; Ken Qin; Zhu Lin; Jiali Peng; He Tian; Yi Yang; Dan Xie; Tian‐Ling Ren (Advanced Science, 2023)
Abstract Lead halide perovskites have made remarkable progress in the field of radiation detection owing to the excellent and unique optoelectronic properties. However, the instability and the toxicity of lead‐based perovskites have greatly hindered its practical applications. Alternatively, lead‐free perovskites with high stability and environmental friendliness thus have fascinated significant research attention for direct X‐ray detection. In this review, the current research progress of X‐ray detectors based on lead‐free halide perovskites is focused. First, the synthesis methods of lead‐free perovskites including single crystals and films are discussed. In addition, the properties of these materials and the detectors, which can provide a better understanding and designing satisfactory devices are also presented. Finally, the challenge and outlook for developing high‐performance lead‐free perovskite X‐ray detectors are also provided.